Risk Factors of Bladder Carcinoma: A Study of Patients Treated at Tishreen University Hospital (2019-2020) - نداف لؤي; حرفوش أيمن; محمد علي (Latakia University Journal -Medical Sciences Series, 2021)
Objective: This study was conducted to estimate risk factors of bladder cancer associated with tobacco, occupational exposure, familial history, chronic infections and alcohol consumption among the patients population at Tishreen University Hospital – Lattakia, Syria. Materials and methods: A retrospective case – control study was conducted among (153 cases and 153 controls). Cases were selected from patients diagnosed in the period of 1/5/2019 - 1/5/2020. Controls were randomly selected from the same setting. Data were collected using interview questionnaire (face to face) or from the patient’s files. The study excluded the patient with loss of information (9) and patients with metastasis to the bladder. Analyses revolved around univariate, bivariate and multivariate logistic regression. Results: The mean age of cases was (63.405 years) and (59.915 years) for controls. The odds of having bladder cancer among smokers was (9.5) times significantly higher in cases VS. controls. The odds of occupational exposure was (6.5) times significantly higher in cases VS. controls. The odds of familial history, chronic infections and alcohol consumption was (5.13-2.2-1.6) respectively. Conclusion: Tobacco and occupational exposure are the most common causes of urinary bladder cancer, while alcohol consumption has not been affirmed as a risk factor of bladder cancer. We advise to develop appropriate prevention policies in order to control this alarming disease in Syria.